More straw bale building : a complete guide to designing and building with straw - Magwood, Chris (Books for living wisely from Mother Earth news., 2005)
"Straw bale building is no longer a fringe idea but has blossomed into a mature and highly developed construction technique that is widely practiced in North America and elsewhere. Houses built from straw bales are straightforward to build, affordable, super energy efficient, environmentally friendly, attractive, and can be designed to match the builder's personal space needs, esthetics, and budget. But, with the evolution of the method, the details of what to avoid and how to achieve acknowledged best practices have also changed." "More Straw Bale Building is designed to meet the changed needs of this remarkable industry. A completely rewritten edition of the 20,000-copy best-seller, Straw Bale Building, it leads the potential builder through the entire process of building a bale structure, tackling all the practical issues: finding and choosing bales; developing sound building plans; roofing; electrical, plumbing, and heating systems; building code compliance; and special concerns for builders in northern climates. The book includes a major amount of new material, as well as new illustrations and photographs." "Down-to earth and complete, More Straw Bale Building makes the remarkable benefits of straw bale building available in the most comprehensive and practical book on the subject to date."--Jacket